Project SULAM: Saving is Fun - Affandi, Salwani; Mohamad Azmin, Nur Azwani (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
The "Saving is Fun" program, initiated by FIN533 students as a SULAM project on June 8, 2023, aimed to instill essential life skills and promote financial literacy among young students. SULAM, which stands for Service-Learning Malaysia- University for Society, is an educational approach that empowers students to apply their knowledge, skills, and competencies to address community issues.